1971
DOI: 10.1203/00006450-197107000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Gaps in Doctor-Patient Communication: Doctor-Patient Interaction Analysis

Abstract: ExtractAs one of several approaches to scientific analysis of doc tor-patient communication, 285 visits to a pediatric walk-in clinic were scrutinized using an expanded version of Bales' Interaction Process Analysis. Data analysis consisted of individual case studies and computer programs for descriptive summaries of cases and index scores. Factor analysis and chi-squarc calculations were among the methods used to test significant relations between attributes of the doctor-patient interaction and the dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
1
4

Year Published

1971
1971
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 194 publications
(66 citation statements)
references
References 5 publications
2
59
1
4
Order By: Relevance
“…Those parents who were asked for their ideas in the treatment planning process were almost unanimously "very satisfied" with the care received and were 4 times more likely than those parents not involved to rate the quality of care as very high. The importance of effective collaboration or partnership with families was first identified by the pioneering work of Korsch and colleagues [40][41]. The use of collaboration is associated with a number of positive treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Those parents who were asked for their ideas in the treatment planning process were almost unanimously "very satisfied" with the care received and were 4 times more likely than those parents not involved to rate the quality of care as very high. The importance of effective collaboration or partnership with families was first identified by the pioneering work of Korsch and colleagues [40][41]. The use of collaboration is associated with a number of positive treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…This part takes place between the adults, with this distribution of child involvement seen in all the studies that reported this information. 19,21,[23][24][25][26]31,36 When a child was asked to present the problem for attendance, one of the studies suggested that this gave a child more opportunity to go on to have some participation in the latter part of the consultation. 23 It has also been shown that if the doctor and child start talking together at the outset of the consultation without the adult carer having had their concerns expressed, this is likely to result in the adult interrupting doctor-child talk.…”
Section: Limited Meaningful Child Involvement In These Consultationsmentioning
confidence: 99%
“…[18][19][20][21]24,26,29,31,36 These studies use different methods to reach these estimates and so are not directly comparable with one another. However, they do show that the child has a limited quantifiable involvement in their own consultation.…”
Section: The Quantitative Amount Of the Child's Involvementmentioning
confidence: 99%
See 2 more Smart Citations